Strategy of the Department of Cooperatives and Small Business of North Sumatra Province in the Development of Cooperatives in North Sumatera - Saidah Ulfah Pohan; Marliyah Marliyah (Jurnal Fokus Manajemen, 2022)
The development of cooperatives is in accordance with the identical development of the people's economy. The welfare of the wider community and together is the basis of the development of Indonesian cooperatives. This research method is a descriptive method, which is an attempt to reveal the actual facts faced by cooperative actors in the North Sumatra region. Cooperatives are developed to realize economic democracy which, among other things, is manifested in the distribution of income in the community through the growth of healthy cooperatives. Cooperatives are driven so that the distribution of ownership of assets (wealth) and business opportunities in society is improved functionally and continuously. Even some experts say that cooperatives are a movement that plays a role in accelerating the process of capital ownership reform.